Desenvolvimento do capim-marandu com altura fixa ou variável durante as estações do ano - Pessoa, Denis Douglas (2016)
Aimed to identify, for assessing the tillering dynamics and morphogenesis , strategy (s ) suitable ( s) defoliation management to optimize the appearance of tillers and biomass of Urochloa Brizantha syn. Brachiaria brizantha cv. Marandu ( marandugrass ) throughout the year. The experiment was conducted from January 2013 to May 2014 were studied three strategies defoliation: Marandugrass with 30 cm throughout the experimental period (constant height); Marandugrass 15 cm in winter, the spring 30 cm and 45 cm in summer (increasing height); and Marandugrass 45 cm in winter, the spring 30 cm and 15 cm in summer (descending height). The experimental design was completely randomized in a split plot in time, with four replications. In winter, in the spring and summer, the following variables were calculated: appearance rate (TApP), mortality (TMoP) and survival (TSoP) of tillers, balance (BAL) between TApP and TMoP, stability index (IE) numbers of tillers and leaf elongation rates and stem, length of leaf blade and stem, leaf senescence rate, phyllochron and duration of life of the sheet. The TAPP was higher in the early spring and summer. For TMoP, the highest values were in the late spring and summer. The balance between TApP and TMoP was negative in winter and late spring, regardless of defoliation strategy. There was no difference in IE between the heights of the canopy during winter and late spring .. The number of tillers was higher in early spring and summer and lower in winter and late spring. The defoliation strategies have not changed phyllochron, leaf elongation rate. In spring and summer, there were increases in the rates of appearance, elongation and leaf senescence and, furthermore, decreased life span and phyllochron sheet. The plant height with increasing showed a lower rate of senescence and lower culm length in the spring. To increase the number of tillers marandu, it is advantageous to handle the plant with increasing height, ie, 15 cm in autumn and winter, the spring 30 cm and 45 cm in summer.The maintaining of B. brizantha cv. Marandu with fixed height of 30 cm or with variations between 15 and 45cm from the fall/winter to summer, does not influence the appearance and the growth of leaves per tiller, which indicates great flexibility on management defoliation in this forage plant.